The Iraq-Kuwait Conflict and the Developmental Scenario to the Peninsula Arab Countries (The Pakistan Development Review, 1991)
The press and news media has dealt with the recent Iraq-Kuwait conflict in an exhaustive manner. This was quite natural because the world is at present witnessing an information explosion, never known to human history before. Despite all this, there are, however, reasons to believe that most of the analysis presented in various dispatches and reports have not been able to deal with the core issues which have escaped the attention of the writers. This was perhaps quite natural because a critical assessment of a certain event can only be done if facts are known and there is in addition a continuous engagement of the experts with the problem under discussion. But this approach may also not be the right one to deal with a crisis which has many a dimension and can, therefore, be looked at from different angles. The crisis under discussion is one which has a global character and can therefore be interpreted in one way or another depending on the writer's own intellectual commitment or vested interests. As such, it is this confusing aspect of the exercise which does not allow a purely objective assessment of the problem. Despite this shortcoming, there, is, however, the desperate need to look at the issue in an objective manner and in conformity with the contemporary spirit governing the various political constellations and their specific thrusts.